CORPORATE SOCIAL RESPONSIBILITY, SOCIAL CAPITAL AND SUSTAINABLE DEVELOPMENT: LESSONS FROM AN INDONESIAN PALM OIL COMPANY - Bhinekawati, Risa (Masyarakat Indonesia, 2018)
This paper reveals that corporate social responsibility (CSR) programs of a large palm oil company can actually build social capital that contribute to sustainable development goals (SDGs). Using an exploratory qualitative case study, this study investigates why and how a company improves social, economic, and social conditions of communities surrounding its palm oil plantations through smallholder farmers empowerment and social capital development, from 1992 to 2011. A case study of a sustainable palm oil company in Indonesia was chosen as an exemplary case study for theoretical or purposive sampling. Primary and secondary data from company documents, media records, interviews and observations were analysed to develop a theoretical model. The study finds that the CSR program is driven by company’s strategic intention to fulfill their business needs by solving the social and environmental issues surrounding its palm oil plantations. Through smallholder farmers’ development program, the company builds social capital that improves social relationship, farmers’ capabilities, and farmers’ access to finance and market; so they are capable to act collectively with the company to achieve economic, social, and environmental performance for both the farmers and the company. This research has created linkages for previously disparate areas of academic enquiry by showing the actual interrelationships between CSR, social capital, corporate sustainability and SDGs.